Otpisani (Epizoda 06) - Kanal . The Written Off, Episode 06 - Channel - Đorđević, Aleksandar (RTV Beograd, 1974)
The sixth episode produces more thrilling suspense as Prle and Tihi plan to enter the main military warehouse complex through the sewers. They know that the Germans will start working on the sewer in two days so they have to move the very next evening. Young Čibi, who is always following Tihi, secretly enters the sewer after the group sets off. They get into the warehouse and lay the explosives, but they are spotted and a skirmish ensues. Meanwhile, the Germans order for water to be released through the sewer for a check up. Tihi’s contact in the plant, Marko, delays this as long as he can. As Tihi’s group escapes, one of the new members is shot but the rest retreat along the sewer while an explosion demolishes the warehouse. In the sewer, the water level is rising and the Germans are still in pursuit, so the partisans split up into three groups taking different exits. The chase follows Tihi and he is wounded, but manages to hide. The workers from the plant are already entering the sewer, but Marko and Čibi find Tihi just in time to take him to the main exit.